(untitled) (Al-Academy, 2020)
The research emphasizes importance of preliminary drawings in design of any product. Therefore, using of simulation as tools for visual thinking in developing drawing and design skills. So that practice of drawing by hand, considering shape of ideas in first stage of visualizations, and practice of its techniques and continuous training.Hence, the research problem arose with the role of simulation method for developing preliminary sketches in the sample of students of the Product Design Department at the College of Design and Art, PNU, as it is important tool for visual thinking that helps the designer in designing and producing innovative artistic works. Therefore, the research axes, a number of findings and recommendations were reached, the important of which is the effective role of applying the simulation method in developing skills in drawing, design and creative thinking, which in turn contributed to enhancing the ability to create artistic products.